Use of Digital Scracth Media to Improve Beginning Reading Skill in Lower Class Primary Schools - Komala; Hadianti, Yeni; Agustin, Mubiar; Cahyani, Isah (PrimaryEdu : Journal of Primary Education, 2024)
There are several problems in reading. Based on findings in the field in several elementary schools, it turns out that the learning methods created by teachers in teaching reading have not been able to encourage children to want to read. This is because the method of learning to read is less interesting in reading so that children have trouble in reading. This research is qualitative research, namely research to describe the problem and research focus. This research aims to determine the use of students' use of the Digital Scratch media learning model in improving beginning reading skills in lower grades. Meanwhile, the data collection technique is triangulated as a data collection technique that combines various existing data collection techniques and data sources, namely through interviews, observation, and documentation so that the answers to problems are clear and detailed. The sample in this research were students in class I and II (low class). Based on the research results, it was concluded that the Scratch digital media learning model can reach the initial reading proficiency level from the initial reading level to the initial reading proficiency level.